Investment megatrends - Froehlich, Robert J. (John Wiley & Sons, Inc., 2006)
There are hundreds of demographic trends developing around the world, and Investment Megatrends explains the dramatic power and influence of these demographic trends on the world of investments. From identifying four prominent global shifts to presenting the number-crunching behind the reasons for their existence, this book provides you with a map of the pitfalls and opportunities of demographic data, what to look for, and where.